THE ROLE OF THE FAMILY ENVIRONMENT IN THE FORMATION OF ALTRUISTIC COMPETENCES (Universal International Scientific Journal, 2026)
This article analyzes the importance of the family environment in the formation of altruistic competencies in a person. The role of family upbringing, parental social behavior, moral values ​​​​in the family and the emotional environment in the development of altruistic qualities in children, such as helping others, empathy and social responsibility, is highlighted based on scientific sources. The results of the study show that a healthy family environment and positive parental role models contribute to the effective formation of altruistic competencies in children.
Keywords: altruism, competence, family environment, upbringing, socialization, empathy, moral values.